Entrepreneurship and family business - Stewart, Alex, 1950-; Lumpkin, G. T.; Katz, Jerome A. (Advances in entrepreneurship, firm emergence and growth ;, 2010)
Volume 12 will consider the timely issue of entrepreneurship and family business. Papers consider the issues, problems, contexts, or processes that make a family firm more entrepreneurial. A representative, but by no means exhaustive, listing of relevant topics includes: the emergence and growth of family businesses; founding conditions unique to family firms; maintaining the entrepreneurial spirit of the founding generation; the role of family in corporate entrepreneurship; the use of entrepreneurial policies, practices and strategies by family firms; outcomes attributable to differences between more and less entrepreneurial family firms; family firm versus non-family firm approaches to entrepreneurial decision making; entrepreneurial characteristics and practices across the generations of a family firm; entrepreneurship as an avenue to strategically renew family firms; the allocation of family-based resources to entrepreneurial endeavors.